The Origins and Chronology of the Usatove Culture - Nikitin, Alexey G.; Ivanova, Svetlana (Archaeologia Lituana, 2022)
Usatove was an important southeast European culture, part of Gimbutas’ kurgan cultures, that connected the world of farmers of Old Europe with the rising influence of steppe nomads at the Eneolithic–Bronze Age transition. While the Usatove culture is currently placed within the late Eneolithic–Early Bronze Age chronological period, emerging evidence suggests the culture formed genetically and culturally in the early part of the 4th millennium BCE. We propose that the biological and cultural foundations of Usatove lie at the juncture of the Suvorove–Novodanylivka branch of the Seredny Stig complex of the North Pontic Steppe, the Trypillian farmers of southeast Europe, with influences from Varna–Karanovo VI–Gumelniţa and late Stone Age cultures of the North Caucasus.